Estudo de seguimento dos casos confirmados de Covid 19 na cidade de Três Corações/MG - Silva, Ranile Dos Santos (2024)
Introduction: The COVID 19 pandemic has imposed several health restrictions on the global population, affecting individual and collective behaviors. In this context, in varied socioeconomic and cultural realities, post-infection behaviors can offer a better understanding of the impact of the pandemic in the short, medium and long term. Objective: To describe the follow-up profile of COVID 19 cases in the municipality of Três Corações, southern Minas Gerais, according to sociodemographic characteristics, pre-existing morbidity and self-reported symptoms of COVID 19. Material and Method: This is an epidemiological and prospective study with a quantitative approach of confirmed cases of COVID 19 reported in the municipality of Três Corações. Cases reported between March 2020 and August 2021 were monitored, with a stratified sample considering sex, age group and hospitalization status. Data collection took place in two phases: initial face-to-face interviews and by telephone, after six months. Specific questionnaires on quality of life (WHOQOL-Bref), anxiety (BAI), social support (MOS-SSS) and post-traumatic stress symptoms (PTSDIES) were applied. Data analysis was conducted using Stata software, comparing indicators between the two moments (T0 and T1). The research was approved by an ethics committee and followed strict ethical standards, ensuring privacy and confidentiality of participants' information. Results: The characterization of the sample of COVID 19 cases showed that these were predominant in women (50.7%), with a higher concentration of cases in the age groups of 40-49 years and 60-69 years (20.7%) in each age group. In addition, 55.3% of the interviewees were people with a partner and 53.3% had completed high school. Most participants were Catholic (53.3%) and 72.7% identified themselves as practicing some religion. Regarding household density, it was predominantly low, with 64.0% of residences housing <0.5 people per room. The majority reported having a “good” or “excellent” relationship with family members (73.3%), while only 13.3% needed a caregiver. Regarding those who were employed, 54.0% had this condition in the last 3 months, while 24.0% were retired. Per capita income was diversified, with 41.2% earning between R$1,000.00 and R$1,800.00. The economic situation was assessed as “good” by 61.4% of respondents. The most common comorbidities were high blood pressure (37.3%), followed by diabetes (28.7%) and asthma/bronchitis (24.7%). Respiratory failure was reported by 12.0% of participants. The perception of quality of life in both the community group and those who were hospitalized increased from an average of 3.9 at baseline (T0) to 4.7 at T1, and satisfaction with health increased from 4.0 to 4.9. Regarding social support between T0 and T1, there was a significant decrease in material support, which went from 18 to 15.8; in terms of affective and emotional support, there was an increase from 13.5 to 13.6 and from 17.9 to 18.2, respectively. PTSD symptoms showed a substantial reduction between T0 and T1 in both groups. In the hospitalized group, the overall score fell from 31.2 to 26.0 and in the community group, from 28.6 to 24.9. Most anxiety symptoms between T0 and T1 decreased and were statistically significant. These results demonstrate a reduction in physical and psychological symptoms, in addition to an improvement in PTSD scores, indicating emotional recovery. There was an increase in social engagement, such as sports and volunteering, although some anxiety symptoms still persisted. The decrease in material support was offset by greater emotional support, highlighting the importance of affective bonds during the crisis. Conclusion: The pandemic affected quality of life and social support, but participants showed signs of adaptation and recovery over time. Improvement in PTSD symptoms and increased social engagement are positive, but persistent anxiety points to the need for continued support to ensure a more complete recovery.